Structural effects of Li and K additives on the columbite precursor and 0.9PMN-0.1PT powders - Bruno, J. C.; Cavalheiro, A. A.; Zaghete, M. A.; Cilense, M.; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Single-phase perovskite 0.9Pb(Mg1/3Nb2/3)O-3-0.1PbTiO(3) (PMN-PT) powders were prepared by using a Ti-modified columbite precursor (MNT) obtained by the polymeric precursor method. The innovation consists in the preparation of Ti-modified columbite in order to react directly with a stoichiometric amount of PbO to obtain pyrochlore-free PMN-PT powders. It has been shown that titanium oxide forms a solid solution with columbite (MN) and does not affect the obtaining of a single-phase columbite precursor. Thus, a high amount of perovskite phase can be obtained by reaction with PbO at 800 degreesC for 2 h. Effects of K and Li additives on the structure of MNT and PMN-PT were studied. X-ray diffraction studies were carried out to verify the phase formation at each processing step and these data were used for structural refinement by the Rietveld method. Both K and Li additives increase the crystallinity of MNT powders, being this effect more intense for the Li-doped samples. For PMN-PT samples the additives cause an insignificant decrease in the amount of perovskite phase. The morphology of the PMN-PT powder depends on the type of the additive. (C) 2003 Elsevier B.V All rights reserved.
Keywords: ceramics; chemical synthesis; powder diffraction; Rietveld; Pb(Mg1/3Nb2/3)O-3